2012
DOI: 10.1007/s00223-012-9572-y
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Urinary N-Telopeptide and Renal Calcium Handling to PTH Infusion after Treatment with Estrogen, Raloxifene, and Tamoxifen

Abstract: This prospective, randomized, placebo-controlled study investigated whether estrogen, tamoxifen, and raloxifene protect the skeleton from the acute catabolic effects of continuous PTH(1-34) infusion. It was infused over 24 h in 25 postmenopausal women both before and while on medication for 16-20 weeks (estrogen n = 7, raloxifene n = 5, tamoxifen n = 7, placebo n = 6). Blood and urine samples were collected at baseline and every 4 h during the PTH(1-34) infusion and analyzed for calcium homeostasis, bone remod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Other studies have shown that administration of raloxifene, categorized as a SERM, significantly attenuated age‐related decrease in eGFR in postmenopausal women, while administration of raloxifene did not result in a significant decrease in serum Pi concentration . Furthermore, estrogen replacement therapy was reported to provide protection against increased serum PTH by attenuating the age‐related decline in eGFR following menopause .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have shown that administration of raloxifene, categorized as a SERM, significantly attenuated age‐related decrease in eGFR in postmenopausal women, while administration of raloxifene did not result in a significant decrease in serum Pi concentration . Furthermore, estrogen replacement therapy was reported to provide protection against increased serum PTH by attenuating the age‐related decline in eGFR following menopause .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that administration of raloxifene, categorized as a SERM, significantly attenuated age-related decrease in eGFR in postmenopausal women, (3) while administration of raloxifene did not result in a significant decrease in serum Pi concentration. (36) Furthermore, estrogen replacement therapy was reported to provide protection against increased serum PTH by attenuating the age-related decline in eGFR following menopause. (36) Although another direct renoprotective mechanism by SERM or estrogen has been speculated, (5) our previous study showed that serum BAP, a reliable marker for bone turnover, (37) was significantly associated with urinary albumin excretion in postmenopausal but not premenopausal women, whereas serum Pi was significantly higher in that postmenopausal population.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogens stimulate osteoblasts to fix calcium, which requires active, carboxylated osteocalcin, which results in a decrease in serum decarboxylated osteocalcin. [172][173][174] TSH levels vary inversely with serum osteocalcin levels. [175][176][177] Serum osteocalcin is directly correlated with tumor growth in both hormone independent and hormone-dependent tumors.…”
Section: Bone Stroma-derived Enzymesmentioning
confidence: 98%